2012
DOI: 10.4194/1303-2712-v12_4_07
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Triplicate groups of 20 European sea bass (35 g) were fed five diets in which the added lipid was 100% fish oil (FO), 40% (CSO40), 60% (CSO60), 80% (CSO80) and 100% (CSO100) refined cottonseed oil (CSO), for a period of 120 days. Overall fish growth, feed conversion ratio and protein utilization were unaffected by dietary treatment, but hepatosomatic and visceral fat indexes increased with increasing dietary CSO. Fillet fatty acid composition of total lipids reflected the fatty acids in the test diets. The mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 46 publications
9
18
0
Order By: Relevance
“…In the present study, by replacing fish oil with rapeseed oil, slight increases in HSI was observed which is in accordance with some other studies (Caballero et al, 2004, Wassef et al, 2007, BeneditoPalos et al, 2007, Piedecausa et al, 2007, Leaver et al, 2008. In many instances, when n-6 PUFA rich alternative oils were used to replace fish oil, the modification of the hepatic lipid content was recorded (Caballero et al, 2004;Wassef et al, 2007;Benedito Paloset al, 2007;Piedecausa et al, 2007;Leaver et al, 2008;Eroldoğan et al, 2012). Increased hepatic lipid deposition is commonly associated with the morphological alteration known as steatosis, which is due to increased synthesis and deposition of triacylglycerols in hepatocyte vacuoles (Montero and Izquierdo, 2010).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In the present study, by replacing fish oil with rapeseed oil, slight increases in HSI was observed which is in accordance with some other studies (Caballero et al, 2004, Wassef et al, 2007, BeneditoPalos et al, 2007, Piedecausa et al, 2007, Leaver et al, 2008. In many instances, when n-6 PUFA rich alternative oils were used to replace fish oil, the modification of the hepatic lipid content was recorded (Caballero et al, 2004;Wassef et al, 2007;Benedito Paloset al, 2007;Piedecausa et al, 2007;Leaver et al, 2008;Eroldoğan et al, 2012). Increased hepatic lipid deposition is commonly associated with the morphological alteration known as steatosis, which is due to increased synthesis and deposition of triacylglycerols in hepatocyte vacuoles (Montero and Izquierdo, 2010).…”
Section: Discussionsupporting
confidence: 79%
“…In a similar study on sea bass, Izquierdo et al (2003) reported that the replacement of 60% of fish oil with linseed oil (n-3 PUFA-rich), soybean oil (n-6 PUFA-rich), rapeseed oil (MUFA-rich) and a mixed-blend did not negatively impact on fish performance, when high lipid content (25%) diets were evaluated. As in many instances, this result is similar to a number of the other earlier studies with European sea bass and salmonids where the complete replacement of dietary fish oil with alternative vegetable oils has resulted in no affect on fish growth performance (Guillou et al, 1995;Tocher et al, 2000;Torstensen et al, 2000;Bell et al, 2001, Mourente et al, 2005bTurchini et al, 2011b;Eroldoğan et al, 2012;Eroldoğan et al, 2013).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In this context, there are two types of alternative oil resources currently studied: terrestial plant oils and microorganism based oils (Pickova and Morkore, 2007;Turchini et al, 2009). Replacement of fish oil by terrestial plant oils such as linseed oil (Wassef et al, 2009), sunflower oil (Merida et al, 2010), palm oil (Fountoulaki et al, 2009), soybean oil (Yıldız andŞener, 2004;Peng et al, 2008), cottonseed oil (Güler and Yıldız, 2011;Eroldoğan et al, 2012), rapeseed oil (Mourente and Bell, 2006) and canola oil (Huang et al, 2007) have been evaluated in marine fish nutrition. Unlike marine microorganism oil sources, terrestial plant oils lack of n-3 LC-PUFA and several negative effects may occur on survival, growth performance, flesh quality and taste parameters of fish fed these diets, including gilthead sea bream (Montero et al, 2008).…”
Section: Introductionmentioning
confidence: 99%